2015
DOI: 10.1371/journal.pone.0130301
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Analysis of the Volatile Faecal Metabolome in Screening for Colorectal Cancer

Abstract: Diagnosis of colorectal cancer is an invasive and expensive colonoscopy, which is usually carried out after a positive screening test. Unfortunately, existing screening tests lack specificity and sensitivity, hence many unnecessary colonoscopies are performed. Here we report on a potential new screening test for colorectal cancer based on the analysis of volatile organic compounds (VOCs) in the headspace of faecal samples. Faecal samples were obtained from subjects who had a positive faecal occult blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 50 publications
0
47
0
1
Order By: Relevance
“…Batty et al . studied 31 faecal samples from normal controls and 31 from a group of high‐risk patients with a high grade adenoma or adenocarcinoma, stratified after colonoscopy performed on the basis of positivity on a faecal occult blood test. SIFT‐MS analysis was performed using each of the three precursor ions available (H 3 O + , NO + , O 2 + ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Batty et al . studied 31 faecal samples from normal controls and 31 from a group of high‐risk patients with a high grade adenoma or adenocarcinoma, stratified after colonoscopy performed on the basis of positivity on a faecal occult blood test. SIFT‐MS analysis was performed using each of the three precursor ions available (H 3 O + , NO + , O 2 + ).…”
Section: Resultsmentioning
confidence: 99%
“…After removal of duplicates and screening for relevant titles, 10 articles were submitted for a full-text analysis and included in this systematic review. Three were related to VOC identified in urine [16][17][18], four in exhaled breath [8,[19][20][21], one in blood [22] and two in faeces [23,24] using different analytical platforms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that both patients with CRC and AA could be discriminated from controls (Table 3). In a second study, fecal VOC profiles of patients with a positive fecal occult blood test (FOBT) were assessed by means of SIFT-MS [50]. By colonoscopy, patients were classified into risk groups (e.g., low risk and high risk) based on their histopathology.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Overall, the pool of metabolites found to be distinct between normal and CRC patients included (a) 3-hydroxybutyric acid, L-valine, L-threonine, 1-deoxyglucose, and glycine [141]; (b) a panel consisting of citrate, hippurate, p -cresol, 2-aminobutyrate, myristate, putrescine, and kynurenate [142]; (c) alanine, citrate, creatine, glutamine, peptide NHs, lactate, leucine, pyruvate, tyrosine, 3-hydroxybutyrate, acetate, formate, glycerol, lipid (−CH 2 –OCOR), the N-acetyl signal of glycoproteins, phenylalanine, and proline [143]; (d) hydroxylated polyunsaturated ultra long-chain fatty acid metabolites [144]; (e) glucose, inositol, hypoxanthine, xanthine, uric acid, and deoxycholic acid [145]; (f) L-valine, 5-oxo-L-proline, 1-deoxyglucose, D-turanose, D-maltose, arachidonic acid, hexadecanoic acid, and L-tyrosine [146]; (g) proline, cysteine, acetate, and butyrate [147]; and (h) L-alanine, glucuronic lactone, and L-glutamine [148]. Most of these metabolites are yet to be validated but might serve as tools for the early detection, prediction, and prognosis of CRC [149152]. …”
Section: Prospective Molecular Markers For Crcmentioning
confidence: 99%